2019–2020 Florida Citrus Production Guide: Alternaria Brown Spot - Megan M. Dewdney (EDIS)
Alternaria brown spot, caused by the fungus Alternaria alternata, affects Minneola tangelos, Dancy tangerines, Murcotts, and less frequently Orlando tangelos, Novas, Lees, and Sunburst. In rare cases, it may also infect grapefruit. Where severe, the disease results in extensive fruit drop and must be controlled on processing and fresh-market fruit. This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Megan M. Dewdney and published by the Plant Pathology Department, March 2019.